Nuclear Medicine in Pediatric Urology - Su Jin Jang (Korean Society of Pediatric Nephrology, 2015)
Renal scintigraphic methods, which are physiologic and minimally invasive, have played important role in the management of various renal diseases in children, providing sensitive tool for early detection of disease even before structural changes become prominent and giving valuable functional and anatomical information to aid medical decision makings in the treatment and follow-up of patients. This review article focuses on the concept and advantages of renal scintigraphy in pediatric patients with various urologic diseases.